Therapeutical investigation of oltipraz in human infection due to S. mansoni - Carvalho, Silvino Alves de; Amato Neto, Vicente; Zeitune, José Murilo Robilotta; Shikanai-Yasuda, Maria Aparecida; Takiguti, Clovis Kiomitsu (Revista do Instituto de Medicina Tropical de São Paulo, 1986)
Seventy two patients with schistosomiasis mansoni, registered in the Infectious and Pa- rasitic Disease Ward, Hospital das Clínicas, Faculty of Medicine, University of São Paulo, were treated iyrith a single oral dose of oltipraz, 30 mg/kg body weight. Their ages ranged from seven to 58 years and eight patients (11.1%) were under fifteen. The main side effects found in this trial were: dizziness 22.2%; drowsiness 21%; nausea 22.2%; headache 9.7%; asthenia 9,7%; paresthesia 8.3%; vomiting 3.3%; abdominal cramps 7.0%; diarrhea 4.2%; dry mouth 2.8%; tender nodules in extremities 2.8°/o; exanthema 2.8%. Other complaints were seen less often. The drug toxicity was evaluated by workout blood counts, kidney function tests (BUN and creatinine), hepatic function test (serum enzymes and bilirubin), EKG and EEG performed before as well as after treat ment. No relevant abnormality was found. Success of therapy was assessed in 49 patients through eight consecutive stool examinations, performed during the six-month period follow ing the drug administration. Both Hoffman's and Kato-Katz's techniques were used. Rectal biopsies were carried out in 20 patients out of 29 whose stool examinations were negative and just one yielded positive, indicating a 5% rate of false negative examinptions. The overall cure rat^ was 59.2%. The present results point out that oltipraz at the used dose levels is relatively efficaceous in the treatment of schistosomiasis mansoni. Its toxic reactions and side effects on the other hand require further investigation.